Satisfaction with Life Scale (SWLS) adapted to work: Psychometric Properties of the Satisfaction with Work Scale (SWWS) - Merino, Mª Dolores; Privado Zamorano, Jesús; Durán, Rocío (Anales de Psicología / Annals of Psychology, 2021)
The purpose of this research has been to adapt the Satisfaction With Life Scale (SWLS) to the work context, giving rise to the Satisfaction With Work Scale (SWWS). To do this, the items were adapted to the work context by modifying the original version of the SWLS as little as possible. A sample of 199 workers from different sectors with an average age of 37.53 years (SD = 12.78 years) was used. Internal, converge and construct validity were analysed, as well as reliability and sex invariance. The results indicate that the SWWS is a valid and reliable measure of cognitive job satisfaction that has the advantage of being brief, general and one-dimensional. Moreover, these results found, open the way to the adaptation of the SWLS to specific contexts such as school, family or couple life, which until now had not been done.